Analytical Method for Development and Validation of Flupirtine Maleate by Reverse-phase High-performance Liquid Chromatography: Analytical Method for Development and Validation of Flupirtine Maleate by Reverse-phase High-performance Liquid Chromatography - Pal, Dilipkumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Background: Flupirtine is a non-opioid analgesic. Flupirtine acts like a N-Methyl-D-aspartate receptor antagonist, yet does not bind to the receptor. Objective: A novel reversed-phase high-performance liquid chromatography (HPLC) method was established to the analysis of flupirtine in raw material and finished products. The purpose of the present research work was to find quantitation of flupirtine by reversed-phase HPLC (RP-HPLC) in tablet dose form. The proposed strategy is approved according to the ICH rules. Materials and Methods: Orthophosphoric acid, HPLC grade methanol, triethylamine, methanol, and chloroform were used. HPLC Column C18 (150 mm Ã— 25.4 mm) with a mobile phase methanol:water (90:10), flow rate of 1 ml/min, was used injection volume 20 Î¼l in run time 20 min. Then we performed method development and its subsequent validation, accuracy and analyte of Robust. Results: All the system suitability parameters were within the limit and a sharp peak with better resolution and purity was obtained with the developed method. Recovery studies are between the ranges of 98.0% and 120% with a relative standard deviation at each level of <2.0%, which proves that the method is accurate for the estimation of flupirtine maleate over the range 50%â€“150% of target concentration. Conclusion: The developed and validated RP-HPLC analysis method is, therefore, recommended to use for routine analysis.